Phenotypic diversity of human adipose tissue-resident NK cells in obesity - Haugstøyl, Martha E.; Cornillet, Martin; Strand, Kristina; Stiglund, Natalie; Sun, Dan; Lawrence-Archer, Laurence; Hjellestad, Iren D.; Busch, Christian; Mellgren, Gunnar; Björkström, Niklas K.; Fernø, Johan (Frontiers in Immunology, 2023)
Natural killer (NK) cells have emerged as key mediators of obesity-related adipose tissue inflammation. However, the phenotype of NK cell subsets residing in human adipose tissue are poorly defined, preventing a detailed understanding of their role in metabolic disorders. In this study, we applied multicolor flow cytometry to characterize CD56bright and CD56dim NK cells in blood and adipose tissue depots in individuals with obesity and identified surface proteins enriched on adipose tissue-resident CD56bright NK cells. Particularly, we found that adipose tissue harbored clusters of tissue-resident CD56bright NK cells signatured by the expression of CD26, CCR5 and CD63, possibly reflecting an adaptation to the microenvironment. Together, our findings provide broad insights into the identity of NK cells in blood and adipose tissue in relation to obesity.